The Christology Of Ho Amnos Tou Theou In The Contextualization Of Johannine Theology: Domba And Adomba In The History of Translation In Indonesia - Andrew Scott Brake (Sekolah Tinggi Theologia Jaffray, 2019)
How do we translate Ho Amnos tou Theou in a context where there is no concept of a sheep, lamb, or goat? How do we communicate the Christology of the Lamb of God? Is Christianity or Christology translatable? If so, has it been translated according to the intention of the writer of the gospel of John? Decisions in translation related to the concept of the Lamb of God have impacted the Christological understanding of the Gospel of John and the nature of Jesus over several decades of contextualization and translation in Indonesia. Indonesia is a nation of many people groups, many languages, and many cultures, some of which are very different from others. How the essence of the original Greek is translated demonstrates much about the missiological motives and principles of the translator as well as the Christological assumptions understood in the Gospel of John, particularly John 1:29. Should the concept of the Lamb, and all the Old Testament background assumed with that identity, be lost in translation simply because there is no such animal as a lamb in the receiving context? This author thinks not, based on a proper understanding of the Johannine conception of that term, and his conception of the identity of Jesus as the Ho Amnos tou Theou. Therefore translators must be wary of allowing the context dictate the translation to the detriment of the essential meaning while also seeking to properly contextualize so that the essential meaning is still communicated in a way that is understandable to the receiving culture. It is outside the scope of this paper to present a comprehensive investigation of all the languages that have been translation in Indonesia. Thus, this paper focuses on the Mee, Dani, Damal, Ngalik, and Moni languages of Papua.